2017
DOI: 10.1002/mp.12240
|View full text |Cite
|
Sign up to set email alerts
|

A method to extract image noise level from patient images in CT

Abstract: Our results demonstrate the signal in the air surrounding an imaging object can accurately be used as a surrogate for the image noise within the object. Our method should enable faster and more robust patient specific image quality assessment due to the lack of the need to segment noise from morphological variations within a patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…A rigorous assessment of the GN algorithm in these exams is needed. The cited references on variations on the GN algorithm 11,12 show promising results of general application of the GN algorithm to clinical CT image data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A rigorous assessment of the GN algorithm in these exams is needed. The cited references on variations on the GN algorithm 11,12 show promising results of general application of the GN algorithm to clinical CT image data.…”
Section: Discussionmentioning
confidence: 99%
“…Malkus et al. used a version of the GN algorithm to measure noise in the air surrounding a patient, and found that this measurement to be a correlated surrogate to region‐of‐interest (ROI) noise measurements in the liver 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies proposed other methods to improve on the ROI-based method, e.g. , by subtracting two adjacent slices (similar to how digital subtraction angiography works) before calculating either a local (pixel-by-pixel) SD, a regional SD, or multiple regional SDs [ 16 19 ]. Such methods are particularly useful in situations where noise does not have a Gaussian distribution, or where pixel value differences exist due to anatomical structures [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has attempted to incorporate image quality measurements on patient CT images in addition to in‐phantom measurements . Several automated algorithms assessing essential image quality metrics on patient CT images and phantom CT images have been demonstrated recently with validated accuracies.…”
Section: Introductionmentioning
confidence: 99%